THE THEORETICAL AND EMPIRICAL SOLUTIONS TO THE PROBLEMS OF GUIDE ACCOMPANIMENT AND TRANSLATION ACTIVITIES (Archive of Conferences, 2022)
This article is devoted to define several problems of tour guides from theoretical and empirical point of view and relevant solutions for them. It also gives information about tourism of Uzbekistan and challenges while interpreting.